A Framework to Investigate Peroxisomal Protein Phosphorylation in Arabidopsis. (April 2019) - Kataya, Amr R.A.; Muench, Douglas G.; Moorhead, Greg B.
Abstract : Peroxisomes perform essential roles in a range of cellular processes, highlighted by lipid metabolism, reactive species detoxification, and response to a variety of stimuli. The ability of peroxisomes to grow, divide, respond to changing cellular needs, interact with other organelles, and adjust their proteome as required, suggest that, like other organelles, their specialized roles are highly regulated. Similar to most other cellular processes, there is an emerging role for protein phosphorylation to regulate these events. In this review, we establish a knowledge framework of key players that control protein phosphorylation events in the plant peroxisome (i.e., the protein kinases and phosphatases), and highlight a vastly expanded set of (phospho)substrates. Highlights: We have cataloged over 100 polypeptides as peroxisomal phospho-proteins using available phospho-proteomic datasets, fully establishing protein phosphorylation as a regulatory mechanism in peroxisomes. Numerous peroxisome-targeted protein phosphatases and kinases have been identified, establishing a framework of key players that control peroxisomal phosphorylation. Phospho-proteins have been identified as components of most peroxisomal processes, many functioning in the fatty acid β-oxidation pathway.